An Early Bronze Age short-cist burial at Abbey Mains Farm, Haddington, East Lothian - Lawson, John A; Henderson, David; Sheridan, Alison (Proceedings of the Society of Antiquaries of Scotland, 2003)
Radiocarbon date of 2570–2300 cal BC from bone, no trace of covering mound.